Sanitation knowledge and practices of Malaysian food SMEs: addressing current issues and readiness in acceptance of green sanitation technology - Khalid, Nurul Izzah; Jalil, Noor Ashikin; Ab. Aziz, Norashikin; Harun, Maizatul Mardiana; Taip, Farah Saleena; Nor-Khaizura, Mahmud Ab Rashid; Sobri, Shafreeza; Yusof, Yus Aniza (INSIGHT - Indonesian Society for Knowledge and Human Development, 2024)
Sanitation is crucial in the food industry, involving cleaning and disinfection processes to ensure facility cleanliness. This study examined sanitation knowledge and practices among small and medium enterprises (SMEs) in Malaysia's frozen meat sector. It also evaluated the acceptance of eco-friendly sanitation technology, specifically an electrolysis unit producing electrolyzed water. Data was collected through an open-ended online questionnaire using Google Forms. The questionnaire comprises demographic profiles, sanitation knowledge, sanitation program design knowledge, sanitation challenges, and the acceptance of integrating a green cleaner with the current sanitation program. Results show SME manufacturers possess sanitation knowledge but face implementation challenges due to absent sanitation programs, skilled labor shortage, hot water supply issues, difficulty cleaning narrow spaces in equipment, chemical storage, and budget constraints. Due to low-temperature operations, only 73 % of frozen meat industries use hot water for sanitation. Additionally, 45 % lack wastewater treatment, leading to chemical residue discharge into municipal drainage. SMEs show interest in electrolyzed water for its dual role as a cleaning and disinfecting agent. The technology's room-temperature efficacy and environmentally friendly degradation into salt and water appeal to SMEs. Adopting electrolysis sanitation technology is expected to significantly reduce costs by utilizing only salt, water, and electricity for electrolyzed water generation.